Clinician-Guided Assessment of Personality Using the Structural Interview and the Structured Interview of Personality Organization (STIPO). Issue 1 (2nd January 2018) - Hörz-Sagstetter, Susanne; Caligor, Eve; Preti, Emanuele; Stern, Barry L.; De Panfilis, Chiara; Clarkin, John F.
ABSTRACT: This article demonstrates the utility of a theory-guided psychodynamic approach to the assessment of personality and personality pathology based on the object relations model developed by Kernberg (1984). We describe a clinical interview, the Structural Interview (SI; Kernberg, 1984), and also a semistructured approach, the Structured Interview of Personality Organization (STIPO; Clarkin, Caligor, Stern, & Kernberg, 2004) based on this theoretical model. Both interviews focus on the assessment of consolidated identity versus identity disturbance, the use of adaptive versus lower level defensive operations, and intact versus loss of reality testing. In the context of a more clinically oriented assessment, the SI makes use of tactful confrontation of discrepancies and contradictions in the patient's narrative, and also takes into account transference and countertransference phenomena, whereas the more structured approach of the STIPO incorporates clinical judgment informed by clinical theory into a well-guided interaction with the patient. Both interviews have good interrater reliability and are coherent with the alternative model for personality disorder diagnosis proposed by the Diagnostic and Statistical Manual of Mental Disorders (5th ed.), Section III. Finally, they provide the clinician with specific implications for prognosis and treatment planning and can rationally guide clinical decision making.